2003
DOI: 10.1046/j.1365-8711.2003.06490.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation pressure cross-sections of fluffy interstellar grains

Abstract: Recent space missions have provided information on the physical and chemical properties of interstellar grains such as the ratio β of radiation pressure to gravity acting on the grains in addition to the composition, structure, and size distribution of the grains. Numerical simulation on the trajectories of interstellar grains captured by Stardust and returned to Earth constrained the β ratio for the Stardust samples of interstellar origin. However, recent accurate calculations of radiation pressure cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…Mukai et al (1992) showed that the ratio β of the forces of radiation and gravity on a grain decreases with increasing porosity for a 1 μm, regardless of grain composition. Saija et al (2003) confirmed this result and emphasized that the decreasing β was limited to ultraviolet and visible wavelengths. Mukai et al (1992) also showed that β increases with porosity for absorptive grains (e.g., magnetite and graphite) with a 1 μm, and it becomes nearly independent of grain size at the highest porosities.…”
Section: Composition and Porositysupporting
confidence: 64%
“…Mukai et al (1992) showed that the ratio β of the forces of radiation and gravity on a grain decreases with increasing porosity for a 1 μm, regardless of grain composition. Saija et al (2003) confirmed this result and emphasized that the decreasing β was limited to ultraviolet and visible wavelengths. Mukai et al (1992) also showed that β increases with porosity for absorptive grains (e.g., magnetite and graphite) with a 1 μm, and it becomes nearly independent of grain size at the highest porosities.…”
Section: Composition and Porositysupporting
confidence: 64%
“…Saija et al (2003) for instance show that the A17, page 12 of 16 fluffiness of the grains tends to decrease their radiation pressure cross-section, as if aggregates behaved like their elemental constituents. This would make grains below the theoretical blowout size less sensitive to radiation pressure, and allow them to remain bound to the star.…”
Section: Blowout Sizementioning
confidence: 99%
“…For particles much smaller than 100 µm radiation pressure gets important (Saija et al 2003;Krauss and Wurm 2004). This is added to the photophoretic force.…”
Section: Fu-orionis Disks and Caismentioning
confidence: 99%